Assessing the Representativeness of Medical Expenditure Panel Survey Inpatient Utilization Data for Individuals With Psychiatric and Nonpsychiatric Conditions. (December 2015) - Slade, Eric P.; Goldman, Howard H.; Dixon, Lisa B.; Gibbons, Brent; Stuart, Elizabeth A
Sampling and reporting biases in the Medical Expenditure Panel Survey (MEPS) survey could render data on inpatient utilization that are not representative for individuals with severe psychiatric conditions. The authors assessed the representativeness of MEPS data on psychiatric inpatient utilization, by comparing MEPS estimates of total annual psychiatric and nonpsychiatric inpatient admissions and bed days, and mean length of stay, for nonelderly U.S. adults in calendar years 2005 to 2010 ( N = 9, 288) to estimates from the Nationwide Inpatient Sample (NIS), a nationally representative inpatient care database derived from hospitals' administrative records ( N = 21, 934, 378). Compared with the NIS, the MEPS indicated 34% as many psychiatric admissions and 86% as many nonpsychiatric admissions, while mean psychiatric length of stay was greater in MEPS than in NIS. In MEPS data, underrepresentation of psychiatric inpatient utilization at community hospitals may result in measurement distortions for commonly used statistics on psychiatric inpatient utilization and costs.